2022
DOI: 10.3390/math10162971
|View full text |Cite
|
Sign up to set email alerts
|

Covariance Matrix Adaptation Evolution Strategy for Improving Machine Learning Approaches in Streamflow Prediction

Abstract: Precise streamflow estimation plays a key role in optimal water resource use, reservoirs operations, and designing and planning future hydropower projects. Machine learning models were successfully utilized to estimate streamflow in recent years In this study, a new approach, covariance matrix adaptation evolution strategy (CMAES), was utilized to improve the accuracy of seven machine learning models, namely extreme learning machine (ELM), elastic net (EN), Gaussian processes regression (GPR), support vector r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Many studies have demonstrated that WOA not only minimizes the cost of solving engineering problems, but also provides better optimization efficiency compared to other population-based metaheuristic algorithms [45,46]. Overall, our results demonstrated that the hybridized models reduced the drawbacks of the standalone ANFIS and enabled a more accurate model Epan, in line with previous studies [14,21,23,31,32,34].…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Many studies have demonstrated that WOA not only minimizes the cost of solving engineering problems, but also provides better optimization efficiency compared to other population-based metaheuristic algorithms [45,46]. Overall, our results demonstrated that the hybridized models reduced the drawbacks of the standalone ANFIS and enabled a more accurate model Epan, in line with previous studies [14,21,23,31,32,34].…”
Section: Resultssupporting
confidence: 89%
“…Therefore, automatic parameter tuning using metaheuristic optimization algorithms has received attention from many researchers studying real-world problems. Examples of the metaheuristic optimization algorithms used for tuning a base method, such as ANN, LSSVM, SVR and ANFIS [23,24], include an electrostatic discharge algorithm [25], a water cycle optimization algorithm (WCA) [26], atom search optimization (ASO) [27], particle swarm optimization (PSO) [28], a cultural algorithm (CA) [29], a bee colony algorithm (BCA) [30], a genetic algorithm (GA) [31], biogeography-based optimization [24], and a firefly algorithm (FFA) [32]. Table 1 compares the hybridized ANFIS models with other ML methods for modeling evaporation as used in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it excels at analyzing nonlinear datasets by utilizing probabilistic approaches and approximating posterior degradation by requiring prior data distribution. The diversity of the covariance function is an essential component of the Gaussian process, which helps to develop tasks with different structures [44][45][46]. Also, the standard property of the GPR model makes this model vital for statistical modeling.…”
Section: Gaussian Process Regression (Gpr)mentioning
confidence: 99%
“…Nonetheless, using statistically based methods to solve a highly non-linear issue such as flyrock and rock fragmentation can be a challenging and difficult endeavor. Many attempts are conducted to solve engineering problems by using artificial intelligence and soft computing techniques [16][17][18][19][20][21][22][23][24][25]. Therefore, the application of intelligent machine learning, such as artificial intelligence (AI) and soft computing (SC), could have relevance and benefit when attempting to solve issues related to this type.…”
Section: Introductionmentioning
confidence: 99%